2000
DOI: 10.1104/pp.122.4.1057
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate Regulation of the Nuclear and Plastidic Genes Coding for the Subunits of the Heteromeric Acetyl-Coenzyme A Carboxylase

Abstract: Plastidic acetyl-coenzyme A (CoA) carboxylase (ACCase) catalyzes the first committed reaction of de novo fatty acid biosynthesis. This heteromeric enzyme is composed of one plastid-coded subunit (␤-carboxyltransferase) and three nuclear-coded subunits (biotin carboxy-carrier, biotin carboxylase, and ␣-carboxyltransferase). We report the primary structure of the Arabidopsis ␣-carboxyltransferase and ␤-carboxyltransferase subunits deduced from nucleotide sequences of the respective genes and/or cDNA. Co-immunopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 85 publications
8
88
1
5
Order By: Relevance
“…Overexpression of BCCP and BC genes proved that coordinated expression of ACCase subunits observed in wild type plants did not include mechanisms capable of adjusting subunits expression to the most abundant ones (Ke et al, 2000). Whereas plants with suppressed plastid ACCase activity clearly showed that seed oil content depends on malonyl-CoA availability in this organelle, the approach depending on one of plastid ACCase subunits overexpression was not able to increase the malonyl-CoA production in plastids.…”
Section: Accase -Essential Enzyme For Oil Production In Plantsmentioning
confidence: 96%
See 1 more Smart Citation
“…Overexpression of BCCP and BC genes proved that coordinated expression of ACCase subunits observed in wild type plants did not include mechanisms capable of adjusting subunits expression to the most abundant ones (Ke et al, 2000). Whereas plants with suppressed plastid ACCase activity clearly showed that seed oil content depends on malonyl-CoA availability in this organelle, the approach depending on one of plastid ACCase subunits overexpression was not able to increase the malonyl-CoA production in plastids.…”
Section: Accase -Essential Enzyme For Oil Production In Plantsmentioning
confidence: 96%
“…The differences between biotin carboxylase and BCCP phenotypes result, most probably, from posttranslational processing of BCCP. Whereas J. Podkowiński, A. Tworak 328 non-biotinylated BCCP molecules are inactive, the whole pool of BC, including transgene originated peptides, is composed of identical, functionally valid molecules.Overexpression of BCCP and BC genes proved that coordinated expression of ACCase subunits observed in wild type plants did not include mechanisms capable of adjusting subunits expression to the most abundant ones (Ke et al, 2000). Whereas plants with suppressed plastid ACCase activity clearly showed that seed oil content depends on malonyl-CoA availability in this organelle, the approach depending on one of plastid ACCase subunits overexpression was not able to increase the malonyl-CoA production in plastids.…”
mentioning
confidence: 96%
“…The dynamic changes in distribution of the ACL mRNAs probably reflect changes in the metabolic demands for cytosolic acetyl-CoA. The pattern of ACLA and ACLB accumulation is nearly indistinguishable from that of cytosolic ACCase mRNA, but is diverse from that of the plastidic ACCase, pyruvate dehydrogenase, and acetyl-CoA synthetase mRNAs (Choi et al, 1995;Ke et al, 1997Ke et al, , 2000aKe et al, , 2000b. These results are consistent with the supposition that ACL generates a cytosolic pool of acetylCoA, which can be carboxylated by the cytosolic ACCase to form malonyl-CoA in the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Other materials collected included leaves between one-third and two-thirds of the final size from 17-d-old plants ("expanding leaves"), flower buds staged according to Bowman (1994), siliques at different stages of development (Ke et al, 2000a(Ke et al, , 2000b, and inflorescence stems of 4-week-old plants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation